Evaluation of Black Head Persian sheep at Malya and West Kilimanjaro Research Centres, Tanzania - Das, S.M. (1991)
Data on Black Head Persian (BHP) sheep, collected at Livestock Research Centres, Malya and West-Kilimanjaro, Tanzania for the period 1964-1988, were analysed. Overall age at first lambing, lambing interval, twinning rate, litter size and annual reproductive rate averaged 784.2± 6.16, 350.9± 3.54 days, 2.8%, 1.03 and 1.19, respectively. Ewes at West-Kilimanjaro were significantly lower in all reproductive traits than ewes at Malya except for age at first lambing. Post-partum weights of BHP ewes at Malya and West-Kilimanjaro averaged 39.45 and 35.73 kg.